Swallowing and swallowing‐breathing interaction as predictors of intubation in Guillain‐Barré syndrome. Issue 2 (20th December 2016) - Ogna, Adam; Prigent, Helene; Lejaille, Michele; Samb, Patricia; Sharshar, Tarek; Annane, Djillali; Lofaso, Frederic; Orlikowski, David
Abstract: Background: Bulbar weakness and respiratory impairment have been associated with increased morbidity in retrospective studies of Guillain‐Barré syndrome (GBS) patients. The aim of this study was to prospectively explore the relationship between subclinical swallowing impairment, respiratory function parameters, the necessity to intubate patients and the development of early postintubation pneumonia in patients with GBS in the intensive care unit (ICU). Methods: Respiratory, swallowing, and tongue strength parameters were measured in 30 consecutive adults (51.7 ± 18.1 years old), hospitalized for GBS in the ICU of a teaching hospital. Twenty healthy volunteers were recruited as a control group. The primary outcomes were intubation and pneumonia during the ICU stay. Results: Nineteen patients (65.5%) had piecemeal swallowing, and 19 (65.5%) had impaired breathing‐swallowing interaction, of which, respectively, 47.4% and 52.6% had a clinically apparent swallowing impairment. Swallowing impairment was associated with lower values of respiratory function, but not with peripheral motor weakness. Tongue protrusion strength was correlated with respiratory parameters and swallowing impairment. Ten patients were intubated and six developed pneumonia. Age, BMI, severe axial involvement, respiratory parameters (vital capacity and respiratory muscle strength), tongue protrusion strength, and clinical swallowing impairment were predictors of intubation. Conclusions: Swallowing impairment was present early after ICU admission in over 80% of patients and was an important predictor of intubation. A systematic clinical evaluation of swallowing should be carried out, eventually combined with an evaluation of tongue protrusion strength, along with the usual assessment of neurological and respiratory function, to determine the severity of the GBS. Abstract : Main factors of intubation in GBS patients. Beside respiratory parameters, swallowing impairment is a very important factor of intubation in GBS patient and should be systematically assessed. Clinical evaluation seems to be sufficient for such assessment.